2018
DOI: 10.1017/jfm.2018.197
|View full text |Cite
|
Sign up to set email alerts
|

Vertical-axis wind turbine experiments at full dynamic similarity

Abstract: Laboratory experiments were performed on a geometrically scaled vertical-axis wind turbine model over an unprecedented range of Reynolds numbers, including and exceeding those of the full-scale turbine. The study was performed in the high-pressure environment of the Princeton High Reynolds number Test Facility (HRTF). Utilizing highly compressed air as the working fluid enabled extremely high Reynolds numbers while still maintaining dynamic similarity by matching the tip speed ratio (defined as the ratio of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 13 publications
(18 reference statements)
8
59
0
Order By: Relevance
“…The rotor was designed to be similar to the one used in the Field Laboratory for Optimized Wind Energy (FLOWE) (Dabiri, 2011). More details related to the experimental campaign can be found in Miller et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…The rotor was designed to be similar to the one used in the Field Laboratory for Optimized Wind Energy (FLOWE) (Dabiri, 2011). More details related to the experimental campaign can be found in Miller et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…In order to compare the effect of the two momentum theories in the DMST, an experimental campaign of VAWT performace was carried out at Princeton's High Reynolds number Test Facility (HRTF). More details related to this campaign can be found in Duvvuri et al (2018) and Miller et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…The Reynolds number for these experiments is defined in terms of the blade chord length, c, as where ν is the kinematic viscosity of water. For all experiments, Re c was 2.7 × 10 4 , which is likely in a transitional regime [21,22].…”
Section: Turbine and Test Facilitymentioning
confidence: 98%
“…It was also found that turbine power output was enhanced by the roughened blade surface below a critical Reynolds number, but degraded above that value. This is indicative of the general sensitivity of cross-flow turbine performance to Reynolds number [21,22]. Here, we evaluate the changes in turbine power output and structural loads as barnacle fouling progresses from initial colonization to maturity.…”
Section: Introductionmentioning
confidence: 99%